Reinforcement of a new calcium phosphate cement with dopamine-mediated strontium-doped calcium polyphosphate-modified polycaprolactone fibers. Issue 108 (9th November 2016) - Liu, Jingwang; Li, Li; Yang, Xu; Huang, ChengCheng; Guo, Chengrui; Gu, Zhipeng; Yu, Xixun
Abstract : To improve the performance of calcium phosphate cement, dopamine/PCL fibers and strontium-doped calcium polyphosphate/D/PCL fibers were respectively incorporated into Sr-containing calcium phosphate cement to develop a novel bone cement. Abstract : To improve some performances of calcium phosphates cement (CPC), such as its mechanical properties, cytocompatibility and bioactivity, in this study, polycaprolactone (PCL) fibers, dopamine (D)/PCL fibers, and strontium-doped calcium polyphosphate (SCPP)/D/PCL fibers were respectively incorporated into Sr-containing calcium phosphate cement (Sr-CPC) for the first time at fiber weight fractions of 0%, 1%, 2% and 5% to develop a novel bone cement. After incubation of the composites in simulated body fluid for 7 days, they were characterized by a three-point bending test for mechanical properties, scanning electron microscopy for morphological observation, a 400 g Gillmore needle with a 1 mm diameter for the setting time, and an MTT test for cytocompatibility. The results indicated that that Sr-CPC reinforced with SCPP/D/PCL fibers had much better mechanical properties and cytocompatibility than pure Sr-CPC. The addition of SCPP/D/PCL fibers into Sr-CPC also dramatically decreased the setting time of cement/SCPP/D/PCL fibers composites. Meanwhile, on the basis of our previous researches, it is expected that this novel bone cement would have a potential efficacy to inhibit aseptic loosening due to the introduction of Sr and SCPP into CPC. The novel SCPP/D/PCL fibers-reinforced Sr-CPC is a promising material for bone substitution.